Comparative Analysis of Apoptosis and Inflammation Genes of Mice and Humans - Reed, John C.; Doctor, Kutbuddin; Rojas, Ana; Zapata, Juan M.; Stehlik, Christian; Fiorentino, Loredana; Damiano, Jason; Roth, Wilfried; Matsuzawa, Shu-ichi; Newman, Ruchi; Takayama, Shinichi; Marusawa, Hiroyuki; et al. (Genome Research, 2003)
Apoptosis (programmed cell death) plays important roles in many facets of normal mammalian physiology. Host-pathogen interactions have provided evolutionary pressure for apoptosis as a defense mechanism against viruses and microbes, sometimes linking apoptosis mechanisms with inflammatory responses through NFκB induction. Proteins involved in apoptosis and NFκB induction commonly contain evolutionarily conserved domains that can serve as signatures for identification by bioinformatics methods. Using a combination of public (NCBI) and private (RIKEN) databases, we compared the repertoire of apoptosis and NFκB-inducing genes in humans and mice from cDNA/EST/genomic data, focusing on the following domain families: (1) Caspase proteases; (2) Caspase recruitment domains (CARD); (3) Death Domains (DD); (4) Death Effector Domains (DED); (5) BIR domains of Inhibitor of Apoptosis Proteins (IAPs); (6) Bcl-2 homology (BH) domains of Bcl-2 family proteins; (7) Tumor Necrosis Factor (TNF)-family ligands; (8) TNF receptors (TNFR); (9) TIR domains; (10) PAAD (PYRIN; PYD, DAPIN); (11) nucleotide-binding NACHT domains; (12) TRAFs; (13) Hsp70-binding BAG domains; (14) endonuclease-associated CIDE domains; and (15) miscellaneous additional proteins. After excluding redundancy due to alternative splice forms, sequencing errors, and other considerations, we identified cDNAs derived from a total of 227 human genes among these domain families. Orthologous murine genes were found for 219 (96%); in addition, several unique murine genes were found, which appear not to have human orthologs. This mismatch may be due to the still fragmentary information about the mouse genome or genuine differences between mouse and human repertoires of apoptotic genes. With this caveat, we discuss similarities and differences in human and murine genes from these domain families.